Related Structures in the Straight Sinus: An Endoscopic Anatomy and Histological Study - Ye, Yuanliang; Ding, Jiuyang; Huang, Shaoming; Wang, Qiujing (Frontiers in Neuroanatomy, 2020)
Some structure might be encountered with endovascular procedures within the straight sinus and is not now readily seen on digital subtraction angiography (DSA). We investigated the morphological and histological characteristics of the straight sinus, chordae willisii (CW), and junction between the great cerebral vein (GCV) and straight sinus. A total of 22 cadaveric heads and 135 patients were analyzed with either anatomic dissection or neuroimaging. The morphological features of the CW and the junction between the GCV and straight sinus were analyzed by endoscope. The histology of the junction between the GCV and straight sinus was evaluated under the microscope with staining for elastic fiber, Masson’s, and immunohistochemistry. We found that fold, elevation, small bugle, or nodule and CW were detected by endoscope in the straight sinus. The most common type of CW was valve-like lamellae, which comprised 40.46% of all CW. Three different types of junctions between the GCV and straight sinus were identified: type 1 has folds in the GCV and elevation on the floor of the straight sinus; type 2 has folds and a small bugle; and type 3 presents with an intraluminal nodule located at the opening of the GCV. Compared with arachnoid granulation, the nodule consists of smooth muscle fibers and higher rate of elastic fibers. Understanding the detailed anatomy of the straight sinus may help surgeons to avoid procedural difficulties and to achieve higher success rate.